2020
DOI: 10.1016/j.envres.2020.109879
|View full text |Cite
|
Sign up to set email alerts
|

Dose effect of Zn and Cu in sludge-amended soils on vegetable uptake of trace elements, antibiotics, and antibiotic resistance genes: Human health implications

Abstract: The application of sewage sludge to agricultural fields reduces the need for mineral fertilizers by increasing soil organic matter, but may also increase soil pollution. Previous studies indicate that zinc and copper, as the most abundant elements in sewage sludge, affect plant uptake of other contaminants. This paper aims to investigate and compare the effect of increasing amounts of Zn and Cu in sludge-amended soils on the accumulation of trace elements (TEs), antibiotics (ABs), and antibiotic resistance gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…More and more studies are linking the application of biosolids to higher levels of resistant bacteria and genes in agricultural soil ( Ross and Topp, 2015 ; Gondim-Porto et al, 2016 ; Burch et al, 2017 ; Lau et al, 2017 ; Murray et al, 2019 ). However, the resistance levels decrease with time after application ( Marti et al, 2014 ; Rahube et al, 2014 ; Ross and Topp, 2015 ; Burch et al, 2017 ; Lau et al, 2017 ; Murray et al, 2019 ), and the current evidence for gene transfer to crops and animals remains inconclusive ( Marti et al, 2013b ; Rahube et al, 2014 ; Lau et al, 2017 ; Murray et al, 2019 ; You et al, 2020 ). Current regulations in the US and the EU do include time restrictions from application to harvesting and/or grazing ( United States Environmental Protection Agency, 1994 , 2003 ; Eur-Lex, 2018 ; Collivignarelli et al, 2019 ).…”
Section: Antibiotic Resistance Gene Removal In Wastewater Treatment Plantsmentioning
confidence: 99%
“…More and more studies are linking the application of biosolids to higher levels of resistant bacteria and genes in agricultural soil ( Ross and Topp, 2015 ; Gondim-Porto et al, 2016 ; Burch et al, 2017 ; Lau et al, 2017 ; Murray et al, 2019 ). However, the resistance levels decrease with time after application ( Marti et al, 2014 ; Rahube et al, 2014 ; Ross and Topp, 2015 ; Burch et al, 2017 ; Lau et al, 2017 ; Murray et al, 2019 ), and the current evidence for gene transfer to crops and animals remains inconclusive ( Marti et al, 2013b ; Rahube et al, 2014 ; Lau et al, 2017 ; Murray et al, 2019 ; You et al, 2020 ). Current regulations in the US and the EU do include time restrictions from application to harvesting and/or grazing ( United States Environmental Protection Agency, 1994 , 2003 ; Eur-Lex, 2018 ; Collivignarelli et al, 2019 ).…”
Section: Antibiotic Resistance Gene Removal In Wastewater Treatment Plantsmentioning
confidence: 99%
“…Considering the interactions between antibiotics, heavy metals, and ARGs in sewage sludge, the use of sewage sludge in agricultural soils is controversial [201], though it meets the demands of farm soils for organic matter and nutrients [202]. The long-term consequences of sewage sludge containing pharmaceutical compounds on soil attributes are not entirely realized.…”
Section: Sewage Sludgementioning
confidence: 99%
“…Trace elements present in both soil and fertilizers play a crucial role in various metabolic and developmental processes throughout a plant's growth. Essential micronutrients such as boron (B), iron (Fe), zinc (Zn), manganese (Mn), magnesium (Mg), copper (Cu), selenium (Se), and molybdenum (You et al, 2020) are indispensable for plant growth (Mishra et al, 2023). Previous studies have indicated that varying copper (Cu) and zinc (Zn) concentrations signi cantly in uence the occurrence of ARGs in edible parts of lettuce (leaves) and radishes (roots).…”
Section: Introductionmentioning
confidence: 99%